Communication Phenomenon Unmarried Career Women in the Pekanbaru City - Reyzakhalis; Welly Wirman; Muhammad Firdaus (International Journal of Media and Communication Research, 2021)
Communication is an absolute necessity for every human being. As social beings, humans cannot but communicate with each other. Along with the development of women's emancipation and experiences that provide something for women moreover have target and self-concept by them own, family standard environment and others. The causes of the increase in unmarried women include high level of education. Opportunity to get a higher education and pursue a career in urban women makes them not in a hurry to make choices for marriage. In this study the authors used the phenomenological method. The data collection techniques uses were through observation, interviews and documentation. The subjects in this study were 3 (three) unmarried career women. The results showed that the motive of future career women with unmarried status in Pekanbaru City is because (because motive), unmarried career women are able to survive, The motive for (in order to motive) in this unmarried career woman is want to be successful and be able to match. Where unmarried career women also want their lives run into harmony. The meaning of unmarried career women in Pekanbaru City is categorized into 2 perspectives. That is how they accept themselves as unmarried and how they convince themselves to live alone without a husband. The career women just need support, good perception of the surrounding environment as well as relatives. Associated with negative communication experiences, like gossip, become a topic of conversation with the family, and marriage topic will be sensitive topic for them.